Treating atopic dermatitis at the source: corrective barrier repair therapy based upon new pathogenic insights. (February 2013) - Elias, Peter M; Sun, Richard; Eder, Angela R; Wakefield, Joan S; Man, Mao-Qiang
Until recently, atopic dermatitis (AD) has been linked to Th1/Th2 cell dysregulation. But now, the opinion that inflammation in AD results from a convergence of inherited and acquired insults to the cutaneous permeability barrier, with variable contributions from inherited abnormalities in innate/adaptive immunity, is becoming increasingly accepted. Current therapy is however, still largely directed towards ameliorating immunologically triggered inflammation, rather than correcting the barrier abnormality. In this article, the authors provide an overview of epidermal barrier function; a review of recent molecular genetic studies pointing to a primary barrier abnormality in AD; a detailed description of new pathogenic insights into AD; and they compare the efficacy of several putative 'barrier repair' products currently utilized as adjunctive or primary therapy for AD. The authors also explore the potential of 'next-generation' barrier repair approaches that attack specific pathogenic mechanisms in AD (high surface pH, elevated serine protease activity, activation of the PAR2 receptor and Staphylococcus aureus secondary infections).